Composition capable of improving sunscreen performance of sunscreen agent, preparation method and application thereof

By combining hydroxyapatite with silk fibroin, sericin and metal ions, a composition that can improve the sun protection performance of sunscreen agents is solved, and the potential harm of existing sunscreen agents to the environment and skin is achieved by achieving efficient and safe sunscreen effects.

CN119770371APending Publication Date: 2025-04-08GUANGZHOU RIDGEPOLE BIOLOGICAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510070761.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-10
Filing Date
2025-01-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing sunscreens are inactivated during photocatalysis, resulting in photochemical degradation and free radical production, and physical filters are potentially harmful to the environment and skin.

Method used

Hydroxyapatite is used to combine with silk fibroin, sericin and metal ions to form a composition that can improve the sun protection performance of sunscreen agents. This composition enhances sun protection effect by improving the dispersion stability and UV absorption properties of hydroxyapatite, while avoiding direct contact between chemical sunscreens and reducing irritation.

Benefits of technology

It significantly improves the sun protection performance of sunscreen, reduces the sensitization and skin irritation of chemical sunscreens, and has a good environment and body-friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770371A_ABST
    Figure CN119770371A_ABST
Patent Text Reader

Abstract

The present invention relates to a composition capable of improving the sunscreen performance of a sunscreen, and a preparation method and application thereof. The preparation method of the composition capable of improving the sunscreen performance of a sunscreen comprises the following steps: mixing and dissolving a metal ion salt and silk fibroin in water to obtain a silk fibroin metal ion complex solution; mixing the silk fibroin metal ion complex solution with hydroxyapatite to obtain a hydroxyapatite silk fibroin metal ion mixed solution; mixing the hydroxyapatite silk fibroin metal ion mixed solution with sericin to obtain the composition capable of improving the sunscreen performance of a sunscreen. The composition has excellent ultraviolet absorption performance, can be compatible with chemical sunscreens, improve the sunscreen performance of the sunscreen, and can avoid direct contact between the chemical sunscreen and the skin, thereby reducing the sensitization and skin irritation of the chemical sunscreen.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to Chinese patent application filed on December 10, 2024 and application number 202411810793.3, the entire contents of which are incorporated by reference into this application. Technical Field

[0002] The present invention belongs to the technical field of cosmetics, and relates to a composition capable of improving the sunscreen performance of a sunscreen agent, and a preparation method and application thereof. Background Art

[0003] Prolonged exposure to UV rays is a contributing factor to a variety of skin diseases. UV radiation includes the portion of the wavelength spectrum between approximately 100 and 400 nm, further divided into UVC (100-280 nm), UVB (280-320 nm) and UVA (320-400 nm). We usually use sunscreens to prevent or mitigate the negative effects of UV radiation. Sunscreens are divided into two major categories: chemical or organic filters, in which the active components are organic molecules that absorb UV rays; and physical or inorganic UV filters, which are physical barriers that reflect radiation. The photocatalytic activity of chemical filters is a major disadvantage. Photocatalytic deactivation leads to their photochemical degradation and the degradation of other components of the sunscreen formulation, as well as the generation of free radicals and other active substances, which themselves may be the cause of certain health problems related to UV radiation. Physical filters, on the other hand, have a certain destructive effect on the environment. At the same time, physical filters can aggravate the condition when applied to damaged or diseased skin.

[0004] In recent years, in-depth research on hydroxyapatite has provided an important direction for the development of sunscreen products. According to experiments, hydroxyapatite has good ultraviolet absorption performance, and its ingredients are friendly to the environment and the human body, and have perfect tolerance to the epidermis. The interior of hydroxyapatite is a loose and porous structure, which can absorb more sunscreens or metal ions as a condition to improve sunscreen performance. Therefore, hydroxyapatite can be used as a substitute for silica and titanium dioxide, while also avoiding the risk of silicosis caused by inhaling too much silica. Therefore, it is very meaningful to develop more sunscreen products containing hydroxyapatite. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a composition capable of improving the sunscreen performance of a sunscreen agent, and a preparation method and application thereof.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composition capable of improving the sunscreen performance of a sunscreen agent, the method for preparing the composition comprising the following steps:

[0008] (1) mixing and dissolving a metal ion salt and silk fibroin in water to obtain a silk fibroin metal ion complex solution;

[0009] (2) mixing the silk fibroin metal ion complex solution with hydroxyapatite to obtain a hydroxyapatite silk fibroin metal ion mixed solution;

[0010] (3) Mixing the hydroxyapatite silk fibroin metal ion mixed solution with sericin to obtain the composition capable of improving the sunscreen performance of the sunscreen.

[0011] The composition for improving the sunscreen performance of the sunscreen involved in the present invention creatively compounds hydroxyapatite with silk fibroin, sericin and metal ions, and the four have a synergistic effect in improving the sunscreen performance of the sunscreen, and silk fibroin and sericin can improve the dispersion stability of hydroxyapatite in the system, making it less likely to aggregate and precipitate, further ensuring the improvement of the sunscreen performance of the sunscreen.

[0012] Metal ions alone do not have ultraviolet absorption properties, but they can promote the ultraviolet absorption properties of the composition for improving the sunscreen properties of the present invention and improve the sunscreen effect of the sunscreen. The method of first mixing the metal ion salt with silk fibroin to form a complex solution and then mixing it with hydroxyapatite can improve the uniformity of the dispersion of the metal ions, further ensuring the improvement of the sunscreen properties of the sunscreen.

[0013] Hydroxyapatite has a loose and porous structure, which can absorb more chemical sunscreens or metal ions as a condition for improving sun protection performance, while avoiding direct contact between chemical sunscreens and the skin, reducing the sensitization and skin irritation of chemical sunscreens.

[0014] Among them, sericin has excellent biocompatibility, low immunogenicity, antioxidant properties, anti-tyrosinase activity, and more importantly, excellent film-forming properties. When used in combination with hydroxyapatite, its film-forming property can further avoid direct contact between chemical sunscreens and the skin, which can greatly reduce the irritation of chemical sunscreens.

[0015] Preferably, the metal ion salt comprises a ferrous ion salt and / or a zinc ion salt.

[0016] The present invention also finds that using ferrous ion salts and / or zinc ion salts as metal ion salts has a better effect of improving the sunscreen performance of sunscreens than other types, and the effect of using ferrous ion salts and zinc ion salts at the same time is further improved.

[0017] Preferably, the mass ratio of metal ions to silk fibroin in the silk fibroin metal ion complex solution is 1:(1-100), for example 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc. Other specific point values ​​within this numerical range can be selected and will not be described here one by one.

[0018] Preferably, in the silk fibroin metal ion complex solution, the mass percentage of metal ions is 0.01-0.5%, for example 0.01%, 0.02%, 0.03%, 0.1%, 0.2%, 0.3%, 0.5% and the like; the mass percentage of silk fibroin is 1-10%, for example 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and the like, and other specific point values ​​within this numerical range can be selected, which will not be described one by one here.

[0019] Preferably, the mixed dissolution in step (1) is stirred for 10-30h (e.g., 10h, 15h, 20h, 25h, 30h, etc.) at pH=5-6 (e.g., pH=5, pH=5.2, pH=5.4, pH=5.6, pH=5.8, pH=6, etc.), 15-35°C (e.g., 15°C, 18°C, 20°C, 22°C, 25°C, 30°C, 35°C, etc.). Other specific point values ​​within the above numerical range can be selected and will not be described one by one here.

[0020] Preferably, the particle size of the hydroxyapatite is 60-4500nm, such as 60nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 400nm, 500nm, 1000nm, 2000nm, 300nm, 4000nm, 4500nm, etc. Other specific values ​​within this numerical range can be selected, which will not be described one by one here. More preferably, it is 100-500nm.

[0021] The present invention also found that the particle size of hydroxyapatite also has a certain influence on the efficacy of the composition that can enhance the sunscreen performance of the sunscreen agent. When the particle size is within the range of 100-500nm, the ultraviolet absorption effect is better.

[0022] Preferably, the mass ratio of hydroxyapatite in step (2) to silk fibroin in step (1) is (100-1000):1, for example 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1, 900:1, 1000:1, etc. Other specific point values ​​within this numerical range can be selected and will not be described one by one here.

[0023] Preferably, the mixing in step (2) is stirred at 15-35°C (e.g., 15°C, 18°C, 20°C, 22°C, 25°C, 30°C, 35°C, etc.) for 6-18h (e.g., 6h, 10h, 13h, 15h, 18h, etc.). Other specific point values ​​within the above numerical range can be selected and will not be described one by one here.

[0024] Preferably, the mass ratio of sericin in step (3) to silk fibroin in step (1) is 1:(10-100), for example 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc. Other specific points within this numerical range can be selected and will not be described in detail here.

[0025] Preferably, the mixing in step (3) is stirred at 15-35°C (e.g., 15°C, 18°C, 20°C, 22°C, 25°C, 30°C, 35°C, etc.) for 6-18h (e.g., 6h, 10h, 13h, 15h, 18h, etc.). Other specific point values ​​within the above numerical range can be selected and will not be described one by one here.

[0026] Preferably, after the mixing in step (3) is completed, the product is freeze-dried to obtain a solid powder.

[0027] When the composition for improving the sunscreen performance of the sunscreen prepared by the present invention needs to be stored for a long time, it can be freeze-dried to be made into solid powder for long-term storage for use.

[0028] In a second aspect, the present invention provides a composition prepared by the preparation method described in the first aspect and capable of improving the sunscreen performance of a sunscreen.

[0029] In a third aspect, the present invention provides a composite sunscreen, the components of which include the composition capable of improving the sunscreen performance of the sunscreen as described in the first aspect and a chemical sunscreen.

[0030] As mentioned above, the composition for improving the sunscreen performance of the sunscreen according to the present invention can be further used in combination with other types of chemical sunscreens and has good compatibility. Hydroxyapatite has a loose and porous structure, which can adsorb chemical sunscreens and avoid direct contact between chemical sunscreens and the skin, thereby reducing the sensitization and skin irritation of chemical sunscreens. The moldability of sericin can further avoid direct contact between chemical sunscreens and the skin, thereby greatly reducing the irritation of chemical sunscreens.

[0031] In a fourth aspect, the present invention provides use of the composition capable of improving the sunscreen performance of the sunscreen agent described in the second aspect or the composite sunscreen agent described in the third aspect in the preparation of a sunscreen product.

[0032] In a fifth aspect, the present invention provides a sunscreen product, comprising 1-15% (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, etc.) by weight of the composition for improving the sunscreen performance of the sunscreen described in the second aspect or the composite sunscreen described in the third aspect.

[0033] Other specific point values ​​within the above numerical range can be selected and will not be described in detail here.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The composition for improving the sunscreen performance of the sunscreen according to the present invention creatively combines hydroxyapatite with silk fibroin, sericin and metal ions, and the four have a synergistic effect in improving the sunscreen performance of the sunscreen.

[0036] (2) Both silk fibroin and sericin can improve the dispersion stability of hydroxyapatite in the system, making it less likely to aggregate and precipitate, further ensuring the improvement of the sunscreen performance of the sunscreen.

[0037] (3) Metal ions alone do not have ultraviolet absorption properties, but they can promote the ultraviolet absorption properties of the composition for improving the sunscreen properties of the present invention and improve the sunscreen effect of the sunscreen. The method of first mixing the metal ion salt with silk fibroin to form a complex solution and then mixing it with hydroxyapatite can improve the uniformity of the dispersion of the metal ions, further ensuring the improvement of the sunscreen properties of the sunscreen.

[0038] (4) Hydroxyapatite has a loose and porous structure, which can absorb more chemical sunscreens or metal ions as a condition for improving sun protection performance, while avoiding direct contact between chemical sunscreens and the skin, reducing the sensitization and skin irritation of chemical sunscreens.

[0039] (5) Sericin has excellent biocompatibility, low immunogenicity, antioxidant properties, anti-tyrosinase activity, and more importantly, excellent moldability. When used in combination with hydroxyapatite, its moldability can further avoid direct contact between chemical sunscreens and the skin, which can greatly reduce the irritation of chemical sunscreens. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a graph showing the evaluation results of the ultraviolet absorption capacity of hydroxyapatite of different particle sizes.

[0041] Figure 2 This is a graph showing the evaluation results of the ultraviolet absorption capacity of hydroxyapatite silk fibroin metal ion complex products. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0043] Example 1

[0044] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen agent, and the preparation method thereof is as follows:

[0045] (1) FeCl2 and ZnCl2 were dissolved in deionized water, the pH of the solution was adjusted to 5.5, and magnetic stirring was performed for 1 h. Then, the silk fibroin aqueous solution was added and stirred at 25°C for 24 h to obtain a silk fibroin metal ion complex solution, wherein Fe 2+ The mass percentage of Zn is 0.08%, 2+ The mass percentage of is 0.08%, and the mass percentage of silk fibroin is 2%.

[0046] (2) The silk fibroin metal ion complex solution of step (1) was mixed with 20 wt % of hydroxyapatite (particle size 200 nm) aqueous dispersion (water content in the dispersion was 80 wt %), and stirred at 25 ° C for 12 h to prepare a hydroxyapatite silk fibroin metal ion mixed solution, wherein the mass ratio of hydroxyapatite to silk fibroin in the system was 665:1.

[0047] (3) Take part of the mixed solution of step (2), add 2 wt % sericin aqueous solution, stir at 25° C. for 12 h, and the mass ratio of sericin to silk fibroin in the system is 1:32. Freeze-dry to obtain a composition that can improve the sunscreen performance of the sunscreen.

[0048] Example 2

[0049] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen agent, and the preparation method thereof is as follows:

[0050] (1) FeCl2 and ZnCl2 were dissolved in deionized water, the pH of the solution was adjusted to 6, and magnetic stirring was performed for 1 h. Then, the silk fibroin aqueous solution was added and stirred at 35 °C for 10 h to obtain a silk fibroin metal ion complex solution, wherein Fe 2+ The mass percentage of Zn is 0.02%, 2+ The mass percentage of silica is 0.18%, and the mass percentage of silk fibroin is 1%.

[0051] (2) The silk fibroin metal ion complex solution of step (1) was mixed with 20 wt % of hydroxyapatite (particle size 500 nm) aqueous dispersion, and stirred at 35° C. for 6 h to prepare a hydroxyapatite silk fibroin metal ion mixed solution, wherein the mass ratio of hydroxyapatite to silk fibroin in the system was 1000:1.

[0052] (3) Add 2 wt% of sericin aqueous solution to part of the mixed solution of step (2), stir at 35° C. for 6 h, wherein the mass ratio of sericin to silk fibroin in the system is 1:10. Freeze-dry to obtain a composition capable of improving the sunscreen performance of a sunscreen.

[0053] Example 3

[0054] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen agent, and the preparation method thereof is as follows:

[0055] (1) FeCl2 and ZnCl2 were dissolved in deionized water, the pH of the solution was adjusted to 5, and magnetic stirring was performed for 1 h. Then, the silk fibroin aqueous solution was added and stirred at 15°C for 30 h to obtain a silk fibroin metal ion complex solution, wherein Fe 2+ The mass percentage of Zn is 0.05%, 2+ The mass percentage of is 0.05%, and the mass percentage of silk fibroin is 10%.

[0056] (2) The silk fibroin metal ion complex solution of step (1) was mixed with 20 wt % of hydroxyapatite (particle size 100 nm) aqueous dispersion, and stirred at 15° C. for 18 h to prepare a hydroxyapatite silk fibroin metal ion mixed solution, wherein the mass ratio of hydroxyapatite to silk fibroin in the system was 100:1.

[0057] (3) Add 2 wt% sericin aqueous solution to part of the mixed solution of step (2), stir at 15° C. for 18 h, wherein the mass ratio of sericin to silk fibroin in the system is 1:100. Freeze-dry to obtain a composition capable of improving the sunscreen performance of a sunscreen.

[0058] Example 4

[0059] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The preparation method thereof is different from that of Example 1 only in that an equal amount of hydroxyapatite with a particle size of 200 nm is replaced with hydroxyapatite with a particle size of 60 nm, and other conditions remain unchanged.

[0060] Example 5

[0061] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The preparation method thereof is different from that of Example 1 only in that an equal amount of hydroxyapatite with a particle size of 200 nm is replaced with hydroxyapatite with a particle size of 4.5 μm, and other conditions remain unchanged.

[0062] Example 6

[0063] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen agent. The preparation method thereof is different from that of embodiment 1 only in that: step (1) is different, FeCl2 is dissolved in deionized water, the pH of the solution is adjusted to 5.5, magnetic stirring is performed for 1 hour, and then a silk fibroin aqueous solution is added, and the mixture is stirred at 25°C for 24 hours to obtain a silk fibroin metal ion complex solution, wherein Fe 2+ The mass percentage of cellulose was 0.16%, and the mass percentage of silk fibroin was 2%. The other steps remained unchanged.

[0064] Example 7

[0065] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen agent. The preparation method thereof is different from that of embodiment 1 only in that: step (1) is different, ZnCl2 is dissolved in deionized water, the pH of the solution is adjusted to 5.5, magnetic stirring is performed for 1 hour, and then a silk fibroin aqueous solution is added, and the mixture is stirred at 25°C for 24 hours to obtain a silk fibroin metal ion complex solution, wherein Zn 2+ The mass percentage of cellulose was 0.16%, and the mass percentage of silk fibroin was 2%. The other steps remained unchanged.

[0066] Comparative Example 1

[0067] This comparative example provides a composition that can improve the sunscreen performance of a sunscreen agent, and the preparation method thereof is as follows:

[0068] (1) A 2% by weight silk fibroin aqueous solution was prepared, the pH of the solution was adjusted to 5.5, and the solution was stirred at 25° C. for 25 h to obtain a silk fibroin solution.

[0069] (2) The silk fibroin solution of step (1) was mixed with 20 wt % of hydroxyapatite (particle size 200 nm) aqueous dispersion, and stirred at 25° C. for 12 h to prepare a hydroxyapatite silk fibroin solution, wherein the mass ratio of hydroxyapatite to silk fibroin in the system was 665:1.

[0070] (3) Add 2 wt % sericin aqueous solution to part of the solution in step (2), stir at 25° C. for 12 h, wherein the mass ratio of sericin to silk fibroin in the system is 1:32. Freeze-dry to obtain a composition capable of improving the sunscreen performance of a sunscreen.

[0071] Comparative Example 2

[0072] This comparative example provides a composition that can improve the sunscreen performance of a sunscreen agent, and the preparation method thereof is as follows:

[0073] (1) Dissolve FeCl2 and ZnCl2 in deionized water (Fe 2+ The mass percentage of Zn is 0.08%, 2+ The mass percentage of the mixture is 0.08%), the pH of the solution is adjusted to 5.5, magnetic stirring is performed for 1 hour to obtain a metal ion solution, and then 20wt% of hydroxyapatite (particle size is 200nm) aqueous dispersion is added, and stirring is performed at 25°C for 12 hours to obtain a hydroxyapatite metal ion mixed solution. The mass ratio of the metal ion solution to the 20wt% hydroxyapatite aqueous dispersion is 1:66.5.

[0074] (2) adding 2 wt % of silk fibroin aqueous solution to the hydroxyapatite metal ion solution prepared in step (1), stirring at 25° C. for 24 h, to prepare a hydroxyapatite silk fibroin metal ion mixed solution, wherein the mass ratio of hydroxyapatite to silk fibroin in the system is 665:1, and the mass ratio of silk fibroin to Fe is 2:1. 2+ The mass ratio of silk fibroin to Zn is 25:1. 2+ The mass ratio is 25:1.

[0075] (3) Add 2 wt% of sericin aqueous solution to part of the complex solution of step (2), stir at 25° C. for 12 h, and the mass ratio of sericin to silk fibroin in the system is 1:32. Freeze-dry to obtain a composition that can improve the sunscreen performance of the sunscreen.

[0076] Comparative Example 3

[0077] This comparative example provides a composition that can improve the sunscreen performance of a sunscreen. The difference between its preparation method and that of Example 1 is that step (3) is not performed, and the hydroxyapatite silk fibroin metal ion mixed solution prepared in step (2) is directly freeze-dried to obtain the obtained composition.

[0078] Comparative Example 4

[0079] This comparative example provides a composition that can improve the sunscreen performance of a sunscreen. The difference between its preparation method and that of Example 1 is that silk fibroin is not added in step (1), and the contents and preparation methods of the remaining components are the same as those of Example 1.

[0080] Comparative Example 5

[0081] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The difference between its preparation method and that of Example 1 is that the mass ratio of hydroxyapatite to silk fibroin in the hydroxyapatite silk fibroin metal ion mixed solution prepared in step (2) is 50:1, and other conditions remain unchanged.

[0082] Comparative Example 6

[0083] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The difference between its preparation method and that of Example 1 is that the mass ratio of hydroxyapatite to silk fibroin in the hydroxyapatite silk fibroin metal ion mixed solution prepared in step (2) is 1200:1, and other conditions remain unchanged.

[0084] Comparative Example 7

[0085] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The difference between the preparation method and that of Example 1 is that in step (3), the mass ratio of sericin to silk fibroin is 1:5, and other conditions remain unchanged.

[0086] Comparative Example 8

[0087] This embodiment provides a composition that can improve the sunscreen performance of a sunscreen. The difference between the preparation method and that of Example 1 is that in step (3), the mass ratio of sericin to silk fibroin is 1:120, and other conditions remain unchanged.

[0088] Test Example 1

[0089] Evaluation of UV absorption capacity of hydroxyapatite with different particle sizes:

[0090] Hydroxyapatite aqueous solutions with particle sizes of 60 nm, 200 nm and 4.5 μm were prepared at a mass concentration of 0.01% respectively, placed in a 96-well plate and tested for ultraviolet absorption in the range of 250-420 nm using an ELISA reader.

[0091] The results are as follows Figure 1 As shown in the figure, it can be seen that hydroxyapatite of different particle sizes has ultraviolet absorption in the ultraviolet wavelength range of 280nm-400nm, and the ultraviolet absorption peak is mainly at 285nm. Among them, hydroxyapatite with a particle size of 200nm has the strongest ultraviolet absorption under the same concentration conditions.

[0092] Test Example 2

[0093] Evaluation of UV absorption ability of hydroxyapatite silk fibroin metal ion complex products:

[0094] The hydroxyapatite silk fibroin metal ion mixture prepared in step (2) of Example 1 (diluted 200 times with water), 0.1wt% hydroxyapatite aqueous solution with a particle size of 200nm, 0.7mg / mL silk fibroin aqueous solution, FeCl2 solution (Fe 2+ concentration 0.01%) and ZnCl2 solution (Zn 2+The ultraviolet absorption ability of five samples (concentration 0.01%) was evaluated and they were placed in a 96-well plate and tested for ultraviolet absorption in the range of 250-420 nm using an ELISA reader.

[0095] The results are as follows Figure 2 As shown in the figure, Fe 2+ or Zn 2+ There is basically no ultraviolet absorption intensity within the wavelength range of 280-400nm, silk fibroin and hydroxyapatite have certain ultraviolet absorption peaks, and the ultraviolet absorption performance of the hydroxyapatite-silk fibroin metal ion complex product is significantly improved, and its effect is significantly better than the superposition effect of silk fibroin and hydroxyapatite. Therefore, in the composition of the present invention that can improve the sunscreen performance of the sunscreen agent, hydroxyapatite, silk fibroin and metal ions have a synergistic effect in improving the ultraviolet absorption performance of the composition.

[0096] Test Example 3

[0097] Dispersion performance evaluation:

[0098] The compositions capable of improving the sunscreen performance of sunscreens of Examples 1-3 and Comparative Examples 3-4 were respectively prepared into 1 wt% aqueous solutions, and a 1 wt% hydroxyapatite aqueous solution was used as a control to observe the sedimentation rate of each group of samples in the solution. The results showed that the 1% hydroxyapatite aqueous solution showed obvious stratification and sedimentation after 10 minutes; the solution of the composition capable of improving the sunscreen performance of sunscreens of Comparative Example 3 began to show slight stratification and sedimentation after 12 hours; the solution of the composition capable of improving the sunscreen performance of sunscreens of Comparative Example 4 began to show slight stratification and sedimentation after 20 minutes; the solution of the composition capable of improving the sunscreen performance of sunscreens of Examples 1-3 began to show slight stratification and sedimentation after 20 hours.

[0099] It can be seen that silk fibroin and sericin can improve the dispersion stability of hydroxyapatite in the system, thereby making the composition for improving the sunscreen performance of the sunscreen agent according to the present invention have good stability, and silk fibroin and sericin have a certain synergistic effect on the above-mentioned effects.

[0100] Application Example 1

[0101] This application example provides a sunscreen lotion, the formula of which is as follows:

[0102]

[0103]

[0104]

[0105] The preparation method is as follows:

[0106] First, weigh and pre-mix the ingredients of each phase according to the formula ratio. After the mixing of each phase is completed, mix the raw materials of phases C, D, and E and stir at 3000 rpm for 20 minutes, slowly add the raw materials of phase B, continue to stir at 3000 rpm for 15 minutes, then add phase A and stir at 3000 rpm for 20 minutes, and finally add phase F and stir for 10 minutes to obtain the sunscreen lotion.

[0107] Application Examples 2-7 and Comparative Application Examples 1-8

[0108] Provided are respectively a sunscreen lotion, the formula of which differs from that of Application Example 1 only in that the composition capable of improving the sunscreen performance of the sunscreen agent in Example 1 is replaced by the compositions capable of improving the sunscreen performance of the sunscreen agent prepared in Examples 2-7 and Comparative Examples 1-8 in equal amounts, the other components remain unchanged, and the preparation method refers to Application Example 1.

[0109] Comparison Example

[0110] A sunscreen lotion is provided, the formula of which is different from that of Application Example 1 only in that an equal amount of the composition capable of improving the sunscreen performance of the sunscreen agent in Example 1 is replaced with water, and other components and preparation methods remain unchanged.

[0111] Test Example 4

[0112] Sunscreen performance evaluation:

[0113] The sunscreen products prepared according to Example 1-7, Comparative Application Examples 1-8 and Control Example were tested for sun protection index (SPF value) and long-wave ultraviolet protection index (PFA value).

[0114] (1) Sun Protection Factor (SPF): Also known as the Sun Protection Factor, it indicates the sun protection effect of sunscreen products. The larger the SPF value, the better the sun protection effect. It is determined based on the minimum erythema dose (MED) of the skin. After using sunscreen products, the minimum erythema dose of the skin will increase, so the SPF of the sunscreen product is:

[0115]

[0116] 160 healthy volunteers aged 18-60 were selected, including 55 males and 105 females. They were randomly divided into 16 groups, with 10 people in each group. Each group tried one of the above sunscreen products. Five points on the back of the subjects were selected to be irradiated with different doses of ultraviolet rays. The lowest irradiation dose that caused erythema on the skin was the minimum erythema dose (MED) of the normal skin of the subject. The test product was evenly applied to the test area of ​​the subject's skin at a dosage of (2.00±0.05) mg / cm 2After waiting for 15 minutes, take 5 points and irradiate with different doses of ultraviolet rays. The lowest irradiation dose that causes erythema on the skin is the MED of the subject's skin under the protection of the product. Calculate the sun protection factor SPF according to the above formula.

[0117] (2) Sunscreen cosmetics long-wave ultraviolet protection index (PFA value): also known as UVA protection index. When UVA in sunlight irradiates the skin, it mainly produces the physiological effect of skin darkening, which is measured by the minimum persistent darkening dose (MPPD). MPPD is the shortest irradiation time required to produce slight darkening of the skin on the entire irradiated area 3 hours after irradiation.

[0118]

[0119] 160 healthy volunteers aged 18-60 were selected, including 55 males and 105 females. They were randomly divided into 16 groups, with 10 people in each group. Each group tried one of the above sunscreen products (the same group of volunteers were used for SPF determination, and the grouping was exactly the same). An irradiation area was selected on the back of the subject and irradiated with ultraviolet rays with a wavelength of 320-400nm. The shortest irradiation time required for slight blackening of the skin on the entire irradiated area after 3 hours of irradiation was the minimum continuous blackening amount MPPD of the normal skin of the subject. In addition, the test product was accurately and evenly applied to the subject's skin in the actual use method, with a dosage of (2.00±0.05)mg / cm 2 After waiting for 15 minutes, irradiate with ultraviolet light with a wavelength of 320-400nm. The shortest irradiation time when the skin turns black is the MPPD of the subject's skin under the protection of the product. Calculate the PFA value according to the above formula. The test results are shown in Table 1:

[0120] Table 1

[0121] Group Average SPF PFA average Application Example 1 35.8 13.6 Application Example 2 35.1 13.2 Application Example 3 34.4 12.5 Application Example 4 28.5 10.6 Application Example 5 29.2 11.3 Application Example 6 31.3 11.8 Application Example 7 32.6 12.1 Comparative application example 1 24.5 8.7 Comparative Application Example 2 22.9 7.9 Comparative Application Example 3 24.3 8.6 Comparative Application Example 4 23.1 8.0 Comparative Application Example 5 21.2 7.3 Comparative Application Example 6 27.0 10.0 Comparative Application Example 7 26.7 9.8 Comparative Application Example 8 25.8 9.2 Comparison example 15.3 6.5

[0122] From the data results in Table 1, it can be seen that the sunscreen product prepared by the composition that can improve the sunscreen performance of the sunscreen agent involved in the present invention has excellent sunscreen performance, and creatively compounding hydroxyapatite with silk fibroin, sericin and metal ions, the four have a synergistic effect in improving the sunscreen performance of the sunscreen agent, and the method of first mixing the metal ion salt with the silk fibroin to form a complex solution and then mixing it with hydroxyapatite can improve the dispersion uniformity of the metal ions, further ensuring the improvement of the sunscreen performance of the sunscreen agent. Compared with application examples 4-7, the effect of application examples 1-3 is relatively better, indicating that the particle size of hydroxyapatite and the formula of metal ions will also have a certain influence on the sunscreen performance of the sunscreen agent.

[0123] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention. The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above-mentioned embodiments. Within the scope of the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0124] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing a composition capable of improving the sunscreen performance of a sunscreen agent, characterized in that: The preparation method of the composition comprises the following steps: (1) mixing and dissolving a metal ion salt and silk fibroin in water to obtain a silk fibroin metal ion complex solution; (2) mixing the silk fibroin metal ion complex solution with hydroxyapatite to obtain a hydroxyapatite silk fibroin metal ion mixed solution; (3) Mixing the hydroxyapatite silk fibroin metal ion mixed solution with sericin to obtain the composition capable of improving the sunscreen performance of the sunscreen agent.

2. The method for preparing a composition capable of improving the sunscreen performance of a sunscreen agent according to claim 1, characterized in that: The metal ion salt includes a ferrous ion salt and / or a zinc ion salt.

3. The method for preparing a composition capable of improving the sunscreen performance of a sunscreen according to claim 1 or 2, characterized in that: The mass ratio of metal ions to silk fibroin in the silk fibroin metal ion complex solution is 1:(1-100); Preferably, the mixed dissolution in step (1) is stirred at pH = 5-6 and 15-35° C. for 10-30 h.

4. The method for preparing a composition capable of improving the sunscreen performance of a sunscreen according to any one of claims 1 to 3, characterized in that: The particle size of the hydroxyapatite is 60-4500 nm, more preferably 100-500 nm.

5. The method for preparing a composition capable of improving the sunscreen performance of a sunscreen according to any one of claims 1 to 4, characterized in that: The mass ratio of hydroxyapatite in step (2) to silk fibroin in step (1) is (100-1000):1; Preferably, the mixing in step (2) is stirred at 15-35° C. for 6-18 h.

6. The method for preparing a composition capable of improving the sunscreen performance of a sunscreen according to any one of claims 1 to 5, characterized in that: The mass ratio of the sericin in step (3) to the silk fibroin in step (1) is 1:(10-100); Preferably, the mixing in step (3) is stirred at 15-35° C. for 6-18 hours; Preferably, after the mixing in step (3) is completed, the product is freeze-dried to obtain a solid powder.

7. A composition for improving the sunscreen performance of a sunscreen prepared by the preparation method according to any one of claims 1 to 6.

8. A composite sunscreen, characterized in that: The components of the composite sunscreen include the composition capable of improving the sunscreen performance of the sunscreen according to any one of claims 1 to 6 and a chemical sunscreen.

9. Use of the composition capable of improving the sunscreen performance of a sunscreen according to claim 7 or the composite sunscreen according to claim 8 in the preparation of a sunscreen product.

10. A sunscreen product, characterized in that: The sunscreen product contains 1-15% by weight of the composition capable of improving the sunscreen performance of the sunscreen according to claim 7 or the composite sunscreen according to claim 8.

Citation Information

Cited By

  • Composite material for loading silk fibroin through hydroxyapatite and preparation method

    CN120983696A

  • A composite material of hydroxyapatite loaded silk fibroin and a preparation method thereof

    CN120983696B